2019
DOI: 10.3389/fmicb.2019.01012
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Pma1p Contributes to Growth, pH Homeostasis, and Hyphal Formation

Abstract: Candida albicans occupies diverse ecological niches within the host and must tolerate a wide range of environmental pH. The plasma membrane H + -ATPase Pma1p is the major regulator of cytosolic pH in fungi. Pma1p extrudes protons from the cytosol to maintain neutral-to-alkaline pH and is a potential drug target due to its essentiality and fungal specificity. We characterized mutants in which one allele of PMA1 has been deleted and the other truncated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…As discussed above, C. albicans inclusion seemed to offer a buffering effect, as shown in the pH increase with the value closer to neutral in the supernatants collected ( Figure 4 ). Such a buffering effect is not unheard of with C. albicans , an organism which prefers to maintain a cytosolic pH range of between 5.8 and 9 [ 81 ]. Lactate and lactic acid are common metabolites of oral bacteria, and often a dysbiosis in the utilization and production of these compounds can lead to disease [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, C. albicans inclusion seemed to offer a buffering effect, as shown in the pH increase with the value closer to neutral in the supernatants collected ( Figure 4 ). Such a buffering effect is not unheard of with C. albicans , an organism which prefers to maintain a cytosolic pH range of between 5.8 and 9 [ 81 ]. Lactate and lactic acid are common metabolites of oral bacteria, and often a dysbiosis in the utilization and production of these compounds can lead to disease [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…This adaptability can potentially be explained by their broader cytosolic pH range. The cytosolic pH range of S. cerevisiae is between 6.0 and 7.0 while in C. albicans the intracellular pH range in vivo is wider, ranging between 5.8 and 9 (Cassone et al, 1983;Kaur et al, 1988;Stewart et al, 1988Stewart et al, , 1989Rabaste et al, 1995;Liu and Kohler, 2016;Tournu et al, 2017;Rane et al, 2019). Their growth is also less affected by an acidic cytosol compared to S. cerevisiae.…”
Section: The Effect Of Fatty Acid Metabolites On Candida Growth and Virulencementioning
confidence: 99%
“…Their growth is also less affected by an acidic cytosol compared to S. cerevisiae. Rane et al (2019) it was shown that C. albicans cells with very acidic cytosols (pH ≤ 5.5) only show minimal growth defects. So SCFA probably exert their inhibitory effect on Candida species not by intracellular acidification alone.…”
Section: The Effect Of Fatty Acid Metabolites On Candida Growth and Virulencementioning
confidence: 99%
“…Removal of Pma1p from the plasma membrane prevents the spike in pH that signals filamentation. Recent work by Ranes et al [214] demonstrated that truncations of C. albicans Pma1p at the C-terminus leads to defects in proper localization and proton pumping activity of Pma1p. Loss of Pma1p function results in an acidification of the cytosol, and reduced filamentation.…”
Section: The Role Of the Vacuole In Secretion And Virulencementioning
confidence: 99%
“…Loss of Pma1p function results in an acidification of the cytosol, and reduced filamentation. Interestingly, the loss of Pma1p function results in hyper-acidification of the vacuole without altering the secretion of Saps and lipases [214].…”
Section: The Role Of the Vacuole In Secretion And Virulencementioning
confidence: 99%